New possibilities of phytotherapy in the treatment of urinary tract infections - S. V. Kotov; A. A. Nemenov; I. D. Boeva (Лечащий Врач, 2021)
The article analyzes the results of the clinical application of the plant phytocomplex which contains extracts of medicinal plants (centaury herbs, lovage roots, rosemary herb and lingonberry leaves), which promotes the normalization of urinary tract function and reduces dysuric disorders, as well as pain syndrome in cystitis and pyelonephritis. At the University Clinic of Urology, Russian National Research Medical University named after N. I. Pirogov in the period from November 2019 to March 2020, a prospective, single-center, randomized study was conducted, which included 60 patients with a diagnosis of acute pyelonephritis. Patients were divided equally into 2 groups: treatment group (n = 30) receiving complex therapy, including empirical antibiotic therapy and a herbal complex for 1 month, and a control group (n = 30) not receiving specific phytotherapy. After 1 month of continuous administration of the drug, the frequency of re-hospitalizations and episodes of hyperthermia was less in the study group. A decrease in the titer of the pathogen and the growth rate of pathogenic microflora, according to urine culture, was observed in treatment group. The specific phytotherapy in the composition of complex therapy allows you to effectively cope with the inflammatory process, as well as reduce the frequency of recurrence of urinary tract infections.